Universal values of sport in senior high school: A comparative study between rural and urban areas - Ali, Burhan; Gumilar, Agus; Martini, Tri; Ma'mun, Amung; Syarifatunnisa, Syarifatunnisa (Jurnal Patriot, 2025)
Problems: There are significant disparities in access to sports facilities, physical education teacher qualifications, and extracurricular programs between rural and urban schools. Purpose: The purpose of this study is to compare the universal values of sports between students from rural areas and students from urban areas in senior high school. Methods: Quantitative descriptive was used in this research with the survey method. This research was conducted using questionnaires as instruments. The study involved 151 high school student respondents; there were 71 students from rural areas and 80 students from urban areas, aged between 14-18 years old. The instrument in this study has 6 indicators and 73 question items, including problem solving, communication, teamwork, discipline, leadership, and fair play, which aims to assess the understanding of universal sports values among senior high school students. Results: The data collected was analyzed using an independent sample t-test with SPSS. The results showed the value of Sig. (2-tailed) > 0.05, meaning that there is no significant difference in the distribution of understanding of values between groups of students from rural and urban areas. Seen in the mean value of rural areas, 451.48, and the mean value of urban areas, 446.63. Conclusion: To follow up on the findings in this study, it is expected to take a larger and more diverse sample to get a more comprehensive picture of the influence of the environment on universal sports values.